Analisis Kemampuan Berpikir Kritis Matematika Siswa Gifted pada materi Bentuk Aljabar - Setiadi, Fathoni Bukhori; Damanhuri, Aceng (International Journal of Progressive Mathematics Education, 2024)
This study aims to analyze gifted students' mathematical critical thinking abilities, and students' constraints that become mistakes in solving problems, as well as the factors that influence the achievement of students' critical thinking skills in solving math problems. The sample of this research is gifted junior high school students who are at SMP Muhammadiyah 08 Jakarta, totaling 3 students. Analysis of critical thinking skills was carried out on items consisting of 5 description questions. This type of research is qualitative. Collecting data with the method of observation, giving questions, documentation, and interviews. The validity of the instrument by testing expert practitioners. The validity test uses a credibility test with data triangulation. The reliability test uses the dependability test. The results of the analysis show that gifted students' critical thinking skills in mathematics are good. This is because all the components of critical thinking indicators are achieved. indicators of students' critical thinking skills such as providing explanations, building basic skills, providing further explanations, setting strategies and tactics, this achievement is supported by the results of the psychological examination criteria which stated that the three students were gifted students with aspects of basic abilities and good personality categories.